Hepatoprotective and Immunostimulatory Effect of Ganoderma, Andrographolide and Turmeric Against Aflatoxicosis in Broiler Chickens - AL-Zuhariy , Mushtaq T.B.; Hassan, Waleed H. (International Journal of Poultry Science, 2017)
Objective: The present study aimed to investigate the toxic effects of Aflatoxin (AF) B1 (AFB1) and evaluate the role of Ganoderma lucidum (GL), Andrographolide (AP) and Turmeric curcuma (CM) in reducing these toxic effects in broiler chickens. Material and methods: A total of 250 (Ross-308) one-day-old broiler chickens were randomly divided into 5 treatment groups (T1-T5) with 50 chicks per group. All groups except for T5 were fed diets that were contaminated with AFs and the groups were treated as follows: T1: Received 0.2% (2 g kg–1) GL as a feed additive. T2: Received 0.2% (2 g kg–1) AP as a feed additive. T3: Received 0.2% (2 g kg–1) CM as a feed additive. T4: Was a positive control (vaccinated but not treated). T5: Was a negative control (not vaccinated or treated). At ages 7, 15 and 25 days, all groups except T5 were vaccinated against Newcastle Disease (ND) (La Sota) and at 12 days, they were vaccinated against Infectious Bursal Disease (IBD) (intermediate D78 strain) (in drinking water). Twenty chicks from each group were challenged with a local virulent ND virus (NDV) isolate (ELD50 105) at 35 days. The AF content was 46.768 ppb in starter diets and 48.661 ppb in the final diet. Results: The GL-fed chicks produced the highest variable antibody titer (Abs), not significant (p<0.05) hepatic and spleen levels of hydrogen peroxide (H2O2) and malondialdehyde (MDA), significantly different (p<0.05) levels of lipid peroxidation (LPO) and highly significant (p<0.05) hepatic and spleen levels of antioxidant defense compounds (Glutathione Reductase (GR) and glutathione peroxidase (GSH-Px)), followed by T3 and T2, respectively, in comparison with T5 and T4. In addition, T1, T2 and T3 showed a significant increase (p<0.05) in Average Daily Gain (ADG) and a significant decrease (p<0.05) in the feed:gain ratio (F:G) compared to T4. However, the Average Daily Feed Intake (ADFI) in the above groups was not significantly different (p<0.05) during the trial period. Conclusion: The study showed the role of GL, AP and CM in reducing the negative effects of AFs by decreasing oxidative stress and immunosuppression in broiler chickens.